Pressure pain sensitivity is associated with dental fear in adults in middle age: Findings from the Northern Finland 1966 birth cohort study - Rami Kankaanpää; Juha Auvinen; Kari Rantavuori; Jari Jokelainen; Jaro Karppinen; Satu Lahti (Blackwell Munksgaard, 2022)
Introduction
Dental fear is a prevalent problem leading to severe deterioration of oral health and health‐related quality of life. Despite the knowledge that dental fear is closely linked to painful experience, the association between pain sensitivity and dental fear remains unclear. This study was designed to evaluate this association with validated measures of dental fear and pressure pain sensitivity in a cohort population.
Methods
The study population consisted of a subpopulation of the Northern Finland Birth Cohort 1966. At the age of 46 years, 1736 participants completed the valid and reliable Modified Dental Anxiety Scale (MDAS) and participated in a clinical examination, where their nonorofacial pressure pain sensitivity was evaluated by validated pressure pain threshold (PPT) and tolerance (PPTo) measurements. Gender‐specific Tobit regressions were performed to analyse this association adjusted for smoking and depressive and anxiety symptoms.
Results
Women with moderate dental fear had 5% (31.3 kPa; P < 0.05), and women with high dental fear had 7% (42.9 kPa; n.s.) lower pressure pain threshold than women with low dental fear. Women with moderate dental fear had 4% (35.4 kPa; P < 0.05) and women with high dental fear had 9% (82.7 kPa; P < 0.01) lower pressure pain tolerance than women with low dental fear. Men with moderate and high dental fear had 3% lower pressure pain tolerance (35.4 kPa; P < 0.05 and 29.6 kPa; n.s., respectively) than men with low dental fear, whereas the associations with pain threshold were not statistically significant. Among women, both anticipatory and treatment‐related dental fears were associated with pain threshold and pain tolerance. Among men, pain threshold was associated with treatment‐related dental fear only and the associations with pain tolerance were not statistically significant.
Conclusions
Nonorofacial pressure pain threshold and tolerance appeared to be lower in participants with dental fear, which emphasizes the role of pain sensitivity in dental fear.